Treatment of postpartum anestrus Sahiwal cows on the basis of VMI and ultrasonography using single injection· of GnRH - SAHU, S K; TIWARl, R P; MISHRA, U K (The Indian Journal of Animal Reproduction, 2023)
Four postpartum anestrus Sahiwal cows which has not shown the signs of estrus even three months after parturition andhaving no corpus luteum in one of the ovaries at two examination made by rectal palpation 11 days apart were selected. Ovaries ofall the animals were monitored at 4 days interval for 24 days by the use of Real-time B-mode ultrasonography machine. Vaginalmucus impedance (VMI) was monitored daily with help of vaginal probe and impedance meter for 24 days. Correlation between VMIand follicular diameter was found to be negative and significant (r = -0.83, P< 0.0 I). On this basis treatment was instituted at lowestpossible probe reading in individual animals using aqueous solution of synthetic analogue of GnRH i.e. Buserelinc acetate, 20 μg(Receptai•, 5ml marketed by Intervet Laboratories Ltd., Pune) after 24 days of monitoring in cows showing a clear increasing anddecreasing trend in VMI. Two animals with VMI values of 21 and 25 showed external signs of estrus at days 19 and 21 post treatmentrespectively. Other two animals with lowest VMI values of 20 and 25 did not show external signs of estrus but one was suspected tobe in silent estrus as indicated by decreasing probe reading. The changes in VMI between pretreatment and post treatment period weresignificant (P< 0.05). The interval between injection and induction was 16.25±2.10 days. It was indicated from the present studythat treatment of postpartum anestrus cows with single injection of GnRH on the basis of VMI and ovarian ultrasonography maygive satisfactory response.
Keywords: Cattle; GnRH postpartum anestrus; ultrasonography; vaginal mucus impedance